Fabrication of polylactic acid/hydroxyapatite/graphene oxide composite and their thermal stability, hydrophobic and mechanical properties. Issue 2 (1st June 2017) - Gong, Ming; Zhao, Qian; Dai, Liming; Li, Yingying; Jiang, Tingshun
Abstract: A series of polylactic acid/hydroxyapatite/graphene oxide composite (PLA/HA/GO) were fabricated via solution blending and casting method using N, N -dimethyl-formamide (DMF) and CH2 Cl2 as mutual solvents. The physicochemical properties of the resulting composites were characterized by means of FT-IR, SEM, TEM, Raman spectra, XRD and N2 -physisorption. Particularly, the thermal stabilities, hydrophobic and mechanical properties of PLA/HA/GO composites were systematically investigated. The influences of GO content on thermal stabilities, hydrophobic and mechanical properties of the composites were also evaluated. The results showed that the addition of GO and HA not only improved the thermal stability of PLA, but also improved the hydrophobic property of PLA-based composites. By compared with the PLA/HA/GO composite, the tensile strength of pristine PLA is slight high. The tensile strength and hardness of PLA/HA/GO composites increased with the increase of GO content. The obtained PLA/HA/GO composite may be a promising material for load-bearing orthopedic implants.